Experience With Routine Vaginal pH Testing in a Family Practice Setting - Adriana J. Pavletic; Stephen E. Hawes; Jenenne A. Geske; Kathy Bringe; Susan H. Polack (Hindawi Limited, 2004)
Background: Despite recommendations by Centers for Disease Control and the American College of Obstetricians and Gynecologists, pH testing is infrequently performed during the evaluation of vaginitis. Consequently, little information exists on its use in a primary care setting.